(untitled) (Pakistan Journal of Medical & Cardiological Review, 2026)
Objective: To evaluate the accuracy of grayscale ultrasonography for gestational age estimation using fetal biometric parameters compared with clinical assessment based on the last menstrual period (LMP). Methods: A cross-sectional study was conducted at the Department of Radiology, DHQ Teaching Hospital Swabi, Pakistan, from January to June 2025. A total of 126 pregnant women aged ≤ 35 years with singleton gestations and a documented LMP were enrolled. Gestational age was estimated sonographically using crown–rump length (CRL), biparietal diameter (BPD), and femur length (FL), and compared with clinical gestational age calculated from LMP. Statistical analysis included descriptive statistics, paired t-tests, and Pearson correlation to assess the relationship between clinical and ultrasound-based gestational age estimates. A p-value <0.05 was considered statistically significant. Results: Gestational age estimated by ultrasonography demonstrated strong positive correlations with clinical assessment. CRL, BPD, and FL showed highly significant correlations with LMP-based gestational age, indicating close agreement between ultrasound and clinical methods. These findings suggest that ultrasound-based estimation provides results comparable to clinical assessment, confirming its reliability and accuracy in obstetric evaluation. Conclusion: Grayscale ultrasonography using standard fetal biometric parameters is a highly accurate and reliable method for gestational age estimation. Its agreement with LMP-based assessment supports its use as a primary tool for pregnancy dating, especially in cases where LMP is uncertain or unreliable, facilitating informed obstetric management